Measurement and propagation models of twisted waves - Muhammad Fairuz Mohamad Kunju (2017)
Since wireless communications was first discovered around 120 years ago [1], it has been increasingly used as a medium for sending and receiving information. Today, the level of dependence on wireless communications in our daily lives is really high. Hence, it is important for us to find new ways of making wireless communications more efficient to fulfil the needs of higher traffic of information transfer that keeps getting higher each day in this fast paced world.